Smoking among immigrant groups in metropolitan France: prevalence levels, male-to-female ratios and educational gradients - Myriam Khlat; Damien Bricard; Stéphane Legleye (BMC, 2018)
Abstract Background Although the French population comprises large and diverse immigrant groups, there is little research on smoking disparities by geographical origin. The aim of this study is to investigate in this country smoking among immigrants born in either north Africa, sub-Saharan Africa or French overseas départements. Methods The data originate from the 2010 Health Barometer survey representative of metropolitan France. The subsample of 20,211 individuals aged 18-70 years (born either in metropolitan France or in the above-mentioned geographical regions) was analysed using logistic regression. Results Both immigrants from sub-Saharan Africa and immigrants from overseas départements were protected from smoking compared to the reference population, and the former had a distinctive strongly reversed educational gradient in both genders. Returned former settlers from the French colonies in North Africa (repatriates) had the highest smoking levels. Natives from the Maghreb (Maghrebins) showed considerable gender discordance, with men having both a higher prevalence (borderline significance) and a reversed gradient and women having lower prevalence than the reference population. Conclusion Immigrants from regions of the world in stage 1 of the cigarette epidemic had relatively low smoking levels and those from regions in stage 2 had relatively high smoking levels. Some groups had a profile characteristic of late phases of the cigarette epidemic, and others, some of which long-standing residents, seemed to be positioned at its early stages. The situation for Maghrebins reflected the enduring influence of gendered norms post-migration. Based on their educational gradients, immigrants from overseas départements (particularly men) and Maghrebin women may be at risk of losing their particularly low prevalence. Immigrants from sub-Saharan Africa could retain it. In-depth analysis of smoking profiles of immigrants' groups is essential for a better targeting of smoking prevention and cessation programs.